1976
DOI: 10.5636/jgg.28.359
|View full text |Cite
|
Sign up to set email alerts
|

Some features of Pc5 pulsations in the period range 180-300 sec.

Abstract: Geomagnetic pulsations with periods between 180 and 300 sec recorded at 7 Canadian magnetic observatories during 1967 were examined to determine the relationships of occurrence, amplitude and period to latitude, time and the level of magnetic activity. Their characteristics are compared with those of long-period Pc5's (periods 300 to 600 sec). Results are examined in the light of existing theoretical models. However, it has been found that these models do not explain satisfactorily the observed evening occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Surprisingly, although one might expect the 4 -10 mHz band to reveal higher frequency field line oscillations at subauroral and/or lower latitudes, very little power in this frequency range was observed during or after these storms at any of these stations. This latitude dependence, consistent with that presented by Gupta [1975Gupta [ , 1976, will be explored further in a subsequent paper.…”
Section: Observations During the March 1998 Stormsupporting
confidence: 81%
See 1 more Smart Citation
“…Surprisingly, although one might expect the 4 -10 mHz band to reveal higher frequency field line oscillations at subauroral and/or lower latitudes, very little power in this frequency range was observed during or after these storms at any of these stations. This latitude dependence, consistent with that presented by Gupta [1975Gupta [ , 1976, will be explored further in a subsequent paper.…”
Section: Observations During the March 1998 Stormsupporting
confidence: 81%
“…Numerous studies have focused on the local time distribution of these long‐period, solar wind‐controlled ULF waves. In the outer magnetosphere, both ground‐based observations [e.g., Gupta , 1975, 1976; Engebretson et al , 1998] and satellite‐based studies [e.g., Kokubun et al , 1989; Anderson et al , 1990; Nosé et al , 1995; Lessard et al , 1999] have shown that they exhibit maximum occurrence and amplitude in the dawn‐to‐noon local time sector, and that in this region, they are predominantly narrow in bandwidth.…”
Section: Introductionmentioning
confidence: 99%
“…The Pc5 pulsation appears for the period of 08:10–08:35 UT (17:10–17:35 LT), when Mineyama is at dusk. Previous studies reported that the Pc5 amplitude is as large as 50–100 nT near a subauroral latitude, but it drastically decreases to <10 nT at a low latitude (<40° GMLAT) (e.g., Gupta, 1976; Lee et al., 2007). The observation in Figure 6b agrees well with the results of the previous studies.…”
Section: Experimental Measurement Of Geomagnetic Fields With MI Senso...mentioning
confidence: 96%
“…For example, using analog data, GUPTA (1975) analysed only the Pc5 pulsations in the 300-600 sec period (1.6-3.3mHz). Similarly, GUPTA (1976) examined only the 180-300 sec (3.3-5.6mHz) Pc5 pulsations. The rationale behind Gupta's work is that "the period range of Pc5's is much too wide and that the characteristics of pulsations in the higher period range differ to some extent from those in the lower end of the range" (GUPTA, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, GUPTA (1976) examined only the 180-300 sec (3.3-5.6mHz) Pc5 pulsations. The rationale behind Gupta's work is that "the period range of Pc5's is much too wide and that the characteristics of pulsations in the higher period range differ to some extent from those in the lower end of the range" (GUPTA, 1976). Using digital data, LAM and RosTOKER (1978) and LAM (1980) analysed the higher frequency spectral band and H.-L. LAM the lower frequency spectral band of Pc5 separately.…”
Section: Introductionmentioning
confidence: 99%